Evolusi Sistem Moneter Internasional Era Standar Emas, Bretton Woods hingga Sistem Nilai Tukar Mengambang - Fatimah Rasyidah Az Zahra; Isti Masruroh; Kuni Naela Rohmah; Sarpini Sarpini (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This article explores the evolution of the international monetary system from the Gold Standard and Bretton Woods to the current floating exchange rate system. The international monetary system has evolved alongside global economic dynamics, starting with the Gold Standard, which ensured exchange rate stability but collapsed due to World War I. The Bretton Woods system introduced a golden era of stable fixed exchange rates and increased global investment but eventually failed due to political and economic instability. The subsequent floating exchange rate system provided flexibility but remained vulnerable to market speculation and fluctuations. This evolution has profoundly impacted international trade, global economic stability, and capital flows, highlighting how each system has significantly shaped global economic dynamics.